2016
DOI: 10.5194/bg-13-737-2016
|View full text |Cite
|
Sign up to set email alerts
|

Primary production in the Chukchi Sea with potential effects of freshwater content

Abstract: Abstract. The in situ primary production rates and various environmental variables were investigated in the Chukchi Sea during the RUSALCA expedition, which was conducted in 2012, to identify the current status of primary production. A 13 C-15 N dual-tracer technique was used to measure the daily primary production rates, which ranged from 0.02 to 1.61 g C m −2 d −1 (mean ±SD = 0.42 ± 0.52 g C m −2 d −1 ). The primary production rates showed large regional differences, with the southern region (0.66 ± 0.62 g C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 45 publications
3
32
0
Order By: Relevance
“…7e and f) Lee et al, 2013). Lee et al ( , 2013 and Yun et al (2016) suggested decreases of primary productivity in the Chukchi Sea in recent years compared to that reported in the 1980s. They hypothesised that the declining trend in primary productivity was associated with changes in water masses, the transport of nutrients with phytoplankton and sediments, primary productivity in the Bering Sea, and the large seasonal, annual, and geographical variation in primary productivity in the Chukchi Sea.…”
Section: Stratification and Primary Productivitymentioning
confidence: 70%
See 1 more Smart Citation
“…7e and f) Lee et al, 2013). Lee et al ( , 2013 and Yun et al (2016) suggested decreases of primary productivity in the Chukchi Sea in recent years compared to that reported in the 1980s. They hypothesised that the declining trend in primary productivity was associated with changes in water masses, the transport of nutrients with phytoplankton and sediments, primary productivity in the Bering Sea, and the large seasonal, annual, and geographical variation in primary productivity in the Chukchi Sea.…”
Section: Stratification and Primary Productivitymentioning
confidence: 70%
“…However, seasonal field measurements in the Chukchi Sea during the ice-free season in summer to autumn indicate a substantial decrease in recent primary productivity compared to estimates in the 1980s (Lee et al, , 2013. Yun et al (2016) speculated that a plausible reason for the recent low primary productivity in the Chukchi Sea could be the decreased concentrations of nutrients and chlorophyll a (Chl a). It should be noted that satellite observations remain uncertain because of the limitations of assessing the productivity beneath the sea surface.…”
Section: Introductionmentioning
confidence: 99%
“…1f-g); see the "Results" section). Data analysis was performed using R (R Core Team, 2014) -employing the zoo (Zeileis and Grothendieck, 2005) and RColorBrewer packages -Ocean Data View (Schlitzer, 2016) and SAS ® software.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was considered that primary production in Young Sound and other Arctic fjords is proportional to the length of the open-water period (Rysgaard et al, 1999) and that future annual primary production across the Arctic will increase as the ice-free season lengthens. However, recent research on the effects of freshening in the Arctic suggest that an increase in freshwater inputs intensifies stratification and impedes the vertical nutrient supply counteracting the effects of a lengthening of the open-water season (Bergeron and Tremblay, 2014;Coupel et al, 2012Coupel et al, , 2015McLaughlin and Carmack, 2010;Yun et al, 2016). Furthermore, freshwater input in the coastal Arctic also brings large sediment loads and/or glacier flour, clouding the water column and affecting the primary productivity via light limitation (Wiktor et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Seaice decline has been linked to enhanced pelagic primary production van Dijken 2011, 2015), mainly due to increased light availability (Nicolaus et al 2012). In contrast, increased freshwater input due to river runoff may result in decreased primary production, because of lower nutrient availability (Yun et al 2016). Besides nutrient supply, other factors are also likely to affect Arctic ecosystem structure, such as oceanic CO 2 uptake and increased temperatures (Tremblay et al 2015).…”
Section: Introductionmentioning
confidence: 99%